في تنمية مهارة القراءة العربية (Think Pair Share - TPS) أثر نموذج فكر–زاوج–شارك - Zahrotul Nur Aini; Mualim Wijaya (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study stems from the limited research on the application of the cooperative learning model “Think–Pair–Share” in developing Arabic reading skills among junior high school students, despite its importance in improving text comprehension and activating classroom participation. The study aims to analyze the effectiveness of the “Think–Pair–Share” model in developing Arabic reading skills, describe its implementation mechanism in the classroom, and measure its effect on improving learning outcomes and the level of female students’ participation. The study adopted Classroom Action Research, and the research sample consisted of 18 eighth-grade female students at State Islamic Junior High School 1 Probolinggo in Indonesia, who were selected purposively. Data were collected using reading tests, observation sheets, and educational documents, then analyzed using a descriptive quantitative approach by calculating means, percentages, and classifying achievement levels. The results showed a noticeable improvement in the female students’ Arabic reading skills after the implementation of the “Think–Pair–Share” model, as the mean score increased from 65 in the pre-cycle stage to 75 in the first cycle and then to 90 in the second cycle. The mastery percentage also increased from 25% to 50%, then reached 100% at the end of the implementation, which aligned with the research objectives and supported social constructivist theory, which emphasizes the role of interaction in knowledge construction. The study concluded that the “Think–Pair–Share” model is effective in developing Arabic reading skills, improving the level of classroom participation, and enhancing interaction in the classroom. The implications of the study lie in its theoretical contribution to the literature on cooperative learning and its practical recommendations for Arabic language teachers regarding the need to adopt interactive teaching strategies. The study also suggests conducting future research to apply the model to other language skills, such as writing, listening, and speaking, and in broader educational contexts.